Funcionalidad familiar y fragilidad del adulto mayor en la institución prestadora de servicios de salud Morona Cocha Jorge Arévalo Melho Iquitos 2022 - Fasanando Siccha, Candy Marangely (2025)
The purpose was to determine the relationship between family functionality and frailty of the elderly in the IPRESS I – 4 Morona Cocha "Jorge Arévalo Melho", Iquitos 2022. The study was descriptive, cross-sectional and non experimental and correlational in design; The study population consisted of 97 people aged 60 years or older, and the sample (78 older adults) was determined through the finite populations formula. Interviews and home visits were used as data collection techniques; and standardized instruments (Family APGAR Questionnaire and Frail's Frailty Scale). The results obtained were: average age of the elderly (72.8 ± 8.3 years), 46.2% had normal family functioning, 34.6% mild family dysfunction and 19.2% severe family dysfunction. Regarding frailty, 59.0% were in a pre-fragile state, 30.7% were fragile, and 10.3% were non-fragile. When correlated, both variables were obtained X2=10.676; df=4; (p=0.030 < 0.05). Concluding that there is significance between family functionality and frailty of the elderly in IPESS I – 4 Morona Cocha "Jorge Arévalo Melho".